2018
DOI: 10.1007/s11130-018-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Native Crocus Taxa as a Great Source of Flavonoids with High Antioxidant Activity

Abstract: Native Crocus taxa are abundant in regions with moderate and dry climate; however, their potential in the food industry has thus far been neglected. The objective of this study was to compare the quantitative and qualitative flavonoid content and antioxidant and cytotoxic activity in organs of several populations of Croatian native taxa and assess their potential for application in the food industry. The dominant flavonoids in the native Crocus taxa were kaempferol and quercetin. Tepals contained similar or hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Additionally, based on this result, we assume that quercetin and kaempferol in broccoli are in an antagonistic relationship with each other during heat stress. Similar relationship between these two flavonols we had previously recorded in Crocus varieties grown at different altitudes [63]. Namely, quercetin:kaempferol ratio was higher in varieties collected at mountains where the UVB radiation was more intense and has a stronger effect on plants.…”
Section: Effect Of Hot-and Cold-water Stress On the Concentration Of ...supporting
confidence: 86%
“…Additionally, based on this result, we assume that quercetin and kaempferol in broccoli are in an antagonistic relationship with each other during heat stress. Similar relationship between these two flavonols we had previously recorded in Crocus varieties grown at different altitudes [63]. Namely, quercetin:kaempferol ratio was higher in varieties collected at mountains where the UVB radiation was more intense and has a stronger effect on plants.…”
Section: Effect Of Hot-and Cold-water Stress On the Concentration Of ...supporting
confidence: 86%
“…Among flavones, myricetin, a molecule diffused and abundant in berries, vegetables, teas and wines, manifests interesting antioxidant, anti-inflammatory and anticancer properties [9,10] and is well recognized for its nutraceuticals value. The strong scavenger activity of myricetin was previously documented; Rusak, et al showed that this compound was able to counteract the 1,1′-diphenyl-2-picrilhydrazyl (DPPH) radicals [11], while Husain, et al demonstrated it was able to scavenge hydroxyl (.OH) radicals generated by UV photolysis of hydrogen peroxide [12]. Moreover, myricetin inhibits liposomes peroxidation [13] and its antioxidant properties appeared higher than Vitamin E (d-α-tocopherol) [14].…”
Section: Introductionmentioning
confidence: 92%
“…developed new natural products to the world population. In this way, scientific researchers are important to plants valorization and conservation (Barreira et al, 2015;Šola et al, 2018). Studies concluded that Rumex obtusifolius present antibacterial activity against Escherichia coli (Harshaw et al, 2010), and procyanidins were isolated and classified from Rumex obtusifolius (Spencer et al, 2007).…”
Section: S H O R T C O M M U N I C a T I O Nmentioning
confidence: 99%